1996
DOI: 10.1002/ecjc.4430790803
|View full text |Cite
|
Sign up to set email alerts
|

Natural observation method for discrete‐time waveforms

Abstract: Tbe natural observation method provides a procedure to analyze the time-varying characteristics of the continuous-time waveform with mathematical rigor and can resolve the fundamental problem encountered in Fourier analysis method. In this paper, for discrete-time waveforms a discrete natural observation method is proposed which has characteristics similar to those for the continuous natural observation method. Similar to the continuous natural observation theory of normal type, the discrete natural observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(e j2π ⋅ f / f s ) of the fundamental observation filter are shown in Eqs. (11) and (12), respectively [7]. Here f s is the sampling frequency.…”
Section: The Natural Observation Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…(e j2π ⋅ f / f s ) of the fundamental observation filter are shown in Eqs. (11) and (12), respectively [7]. Here f s is the sampling frequency.…”
Section: The Natural Observation Transformmentioning
confidence: 99%
“…The authors have reported the first examples of the application of waveform analysis based on the natural observation theory to electromagnetic signals [3,4], and have shown that this method is extremely effective for nonsteady irregular signals such as natural electromagnetic fluctuations. In related research, there are few if any application examples, although Iijima and colleagues provided a deep theoretical study [1,2,[5][6][7][8] of the aspectum has been offered theoretically, but no specific examples of its use for actual waveforms are available. Thus, it is important to examine the characteristics of waveform analysis with the aspectum by applying it to known signals.…”
Section: Introductionmentioning
confidence: 99%
“…The natural observation theory [10][11][12][13][14][15][16][17] is a novel approach to signal analysis dealing with instantaneous variation of signals. That is, while Fourier analysis or the maximum entropy method is an analytical tool that decomposes signals into their frequency components [18], in the natural observation method, signals are expanded as series in the gradients (derivatives) of nonperiodic waveforms.…”
Section: Introductionmentioning
confidence: 99%